Fungal, oomycete, and plasmodiophorid diseases of potato - Adolf, Birgit; Andrade-Piedra, J.L.; Molina, F.; Przetakiewicz, J.; Hausladen, H.; Kromann, P.; Lees, A.K.; Lindqvist-Kreuze, H.; Pérez, W.; Secor, G.A. (Springer, 2020)
This chapter discusses the major potato diseases worldwide: late blight, early blight, wart, and powdery scab. Late blight, caused by the oomycete Phytophthora infestans, continues to be the main biotic constraint of potato production. Annual losses have been estimated to be about €6.1 billion, with major consequences to food security, especially in developing countries. Symptoms of the disease can be seen in leaves (water-soaked light to dark brown spots), stems (brown spots), and tubers (slightly depressed areas with reddish-brown color). High humidity and mild temperatures are essential for disease development and, under optimal conditions, the disease can destroy a field in a few days. Phytophthora infestans evolves continuously, mainly through recombination and migration from other areas. Thus, monitoring of P. infestans populations is critical for the design of effective management strategies. Fungicides remain as the most common tactic for late blight management, but environmental considerations are increasing the pressure to use host resistance, sanitation, and other measures. New solutions being developed to manage late blight include, among others, smart phone-based decision support systems linked to portable molecular diagnostics kits that can disseminate disease information rapidly to a large number of farmers. Emerging research topics on P. infestans include the role of the pathogen–microbiota interaction in promotion or suppression of the disease, as well as the metabolism of P. infestans.